2021
DOI: 10.3390/su13063015
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of a Clay Soil Using Cementing Material from Spent Refractories and Ground-Granulated Blast Furnace Slag

Abstract: Nowadays, huge amounts of refractory materials are generated around the world. The majority of them lack valorization methods. This study analyzes the ability of a doloma and two magnesia spent refractory wastes as soil stabilizers on their own, as well as when combined with Ground-Granulated Blast Furnace Slags (GGBS). These materials showed a limited ability for the soil’s plasticity modification from a plasticity index of 15.6 to a minimum of 12.7. The high pH of the additives increased the soil’s pH from 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…The strength of soil is a measure of its ability to absorb forces without collapsing [ 6 , 7 ]. A soil’s ability to bear normal and shear pressures can be used to determine its strength [ 65 , 71 , 72 ].…”
Section: Soil Stabilization By Conventional Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The strength of soil is a measure of its ability to absorb forces without collapsing [ 6 , 7 ]. A soil’s ability to bear normal and shear pressures can be used to determine its strength [ 65 , 71 , 72 ].…”
Section: Soil Stabilization By Conventional Methodsmentioning
confidence: 99%
“…Another issue in civil engineering is clayey soil [ 4 , 5 ]. Clayey soil is a global issue, causing several difficulties for civil engineers, building enterprises, and property owners [ 6 , 7 , 8 ]. Clayey soils are seen as a potential natural hazard capable of wreaking havoc on engineering buildings [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By incorporating industrial by-products, economic benefits are provided, and they also contribute to a more sustainable approach to soil stabilization, effectively reducing the carbon footprint (Behnood 2018 ; Xu and Yi 2019 ). Therefore, numerous new research challenges have been undertaken to develop environmentally friendly stabilizers based on these innovative materials (Nidzam and Kinuthia 2010 ; Wilkinson et al 2010a , b , James and Pandian 2016 ; Brand and Fanijo 2020 ), such as ground granulated blast furnace slag (GGBFS) (Obuzor et al 2012 ; Hossein Rafiean et al 2020 ; Seco et al 2021 ), basic oxygen furnace slag (BOFS) (Poh et al 2006 ; Mahieux et al 2009 ; Kambole et al 2017 ), button fly ash (Yoon et al 2009 ), and cement kiln dust (Mosa et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The combination of lime and pozzolana produces higher shear strength parameters than expansive clay. [8] found that limestone is effective in stabilizing high-plasticity clays and expansive clays. It is evidenced by the increase in the results of the unconfined compression test, and the liquid limit value decreased and the plastic limit value increased.…”
Section: Introductionmentioning
confidence: 99%